Evaluating the feasibility of "Friends in Nature," a complex nature-based social intervention to address loneliness and quality of life in six cities worldwide - Vert, Cristina; Litt, Jill S; Gascon, Mireia; Roqué, Marta; Masó-Aguado, Montse; Opacin, Nerkez; Garcia, Gabriela; Jansson, Anu; Cattaneo, Lucie; Bártová, Alžběta; Briones-Buixassa, Laia; Carbó, Aina; et al. (Pilot and feasibility studies, 2024)
BACKGROUND: Loneliness, a major public health concern, could be alleviated through social interventions with nature contact as a primary component. "Friends in Nature" is a complex nature-based social intervention designed to be implemented as part of "Reimagining Environments for Connection and Engagement: Testing Actions for Social Prescribing in Natural Spaces" (RECETAS). This project aims to alleviate loneliness and promote health-related quality of life in six different geographic areas worldwide. Feasibility studies are crucial to assess the viability of complex interventions and study procedures before conducting definitive studies. This paper aims to describe the design, implementation, and evaluation of the six-related feasibility studies on the "Friends in Nature" intervention. These studies specifically evaluate feasibility of recruitment and study procedures, intervention implementation, and data collection and distribution. METHODS: We defined a comprehensive set of indicators to assess the feasibility of "Friends in Nature." For the first domain, recruitment procedures were assessed to determine their adequacy, while attrition rates were examined to assess participant retention. For the second domain, the implementation of interventions was evaluated, along with the study design's ability to adapt to unexpected situations and participant adherence to the intervention. Finally, for the third domain, completion rates and the acceptability of the study activities were also analyzed. The feasibility of using specific scales to assess loneliness and well-being was also explored. RESULTS: The feasibility indicators defined for this study were useful to assess the feasibility of "Friends in Nature." Recruitment procedures were generally found to be adequate, and the number of dropouts was low. Interventions were implemented with minor adjustments, and facilitators played a vital role in the well-functioning of the interventions. Although some unexpected situations occurred during the study, adaptations were made, and participants were generally satisfied with the activities proposed. Scales used to assess loneliness and quality of life showed potential for measuring the effects of nature-based social prescribing in the full trial. CONCLUSION: This paper offers valuable insights into the design and execution of feasibility studies for complex interventions like "Friends in Nature." Findings from these assessments explore the feasibility of "Friends in Nature" and will inform the main RECETAS studies, which are designed to strengthen the evidence base to support the use of nature-based social prescribing to reduce loneliness and promote quality of life. TRIAL REGISTRATION: Barcelona trial: NCT05488496, Prague trial: NCT05522140, and Helsinki trial: NCT05507684.